Synthesis and antiproliferative activity of 3-(substituted)-4,5,6,7-tetrahydro-6-(substituted)-1H-pyrazolo[3,4-c]pyridine derivatives - Pawar, Chandrakant; Pansare, Dattatraya; Shinde, Devanand (European Journal of Chemistry, 2017)
A series of new molecules having 3-(substituted)-4,5,6,7-tetrahydro-6-(substituted)-1H-pyrazolo[3,4-c]pyridine and 3-(substituted)-5,6-dihydro-6-(substituted)-1H-pyrazolo[3,4-c] pyridin-7(4H)-one derivatives were designed and synthesized in large scale (grams range). The structures of the synthesized compounds were elucidated and confirmed by 1H NMR, 13C NMR, Mass spectra; and purity was also checked through LC/MS and HPLC analysis. The antiproliferative activity of the compounds was checked for lung cancer, cervical cancer, breast cancer and prostate cancer on panel of four cell lines. A few compounds (13c, 13g, 15g and 15h) showed promising antiproliferative activity in the range of 5.12-17.12 µM which were further tested for their inhibitory activity against panel of 8 human kinases at 10 µM concentrations. The compounds 13c, 13g, 15g and 15h shows prominent inhibitory activity against Aurora-A, Aurora-B, CDK5/P25 and mTOR kinases.